A SUSPICION OF ARCHITECTONIC IN KANT'S TRANSITION PROJECT. Issue 5 (3rd September 2019) - Thomson, Terrence
Abstract: This essay explores the undervalued methodological elements underpinning Kant's Transition from Metaphysical Foundations of Natural Science to Physics in Opus postumum . I do this by drawing a line between the Architectonic of Pure Reason in Critique of Pure Reason and the Transition, although this line is problematized at various points. What emerges is the call for an explicitly architectonic understanding of the concept of transition in Opus postumum . According to the architectonic of Transition, instead of only devising the strict division of metaphysics and physics we must devise systematic ways of building bridges between them and finding their points of interconnection. When extended to the wider critical edifice this implies a radical departure from the Architectonic of Pure Reason as it was understood in Critique of Pure Reason and a complication of Kant's theorization of metaphysics, physics, and physiology throughout his corpus.